Habitat Suitability in High Andean Butterflies: The Role of Land Cover in the Occurrence and Conservation of Species - Méndez-Zambrano, María Alejandra; Fajardo Medina, Gonzalo Ernesto (Neotropical entomology, 2024)
High Andean butterflies in northern South America are subject to landscape change processes. Our study used models to assess the habitat suitability of three Satyrinae species in the Upper Bogotá River Basin, Colombia. These three species include Pedaliodes polla (Thieme), Pedaliodes phaea (Hewitson), and Pedaliodes phaeina (Staudinger), the last two are endemic to Colombia. We used MaxEnt software to assess the habitat quality of these species, analyze the bioclimatic requirements that most influence them, and propose priority conservation areas. Our results indicated that, in most cases, the contribution of cover is more significant than 60%, so this variable determines the habitat capacity to support the species under study. We identified that the areas with suitable habitats are reduced with values less than or equal to 25% and are located in areas with a medium degree of intervention, which allows the species to occur. On the other hand, the climatic variables with the most significant contribution to the models were Temperature Seasonality and Precipitation of Driest Quarter (May–July). Conservation efforts must be focused on the most suitable areas, given the reduction in habitat for these species. Our research emphasizes the need to safeguard well-connected remnants of the high Andean forest and natural cover in agricultural matrices to counter the impact of agricultural expansion.